2015
DOI: 10.1155/2015/702631
|View full text |Cite
|
Sign up to set email alerts
|

How Predictable Is the Operative Time of Laparoscopic Surgery for Ovarian Endometrioma?

Abstract: Endometriosis is a tricky albeit common disease whose management largely relies on laparoscopy. We have studied the operative times of laparoscopic endometrioma surgery in order to assess their predictability and possible predictors. One hundred forty-eight laparoscopies were included, with a median operative time of 70 minutes (mean 75.14; 95% CI: 70.03–80.24). Half of the cases had a duration within 15–20 minutes above or below the median (IQR: 55–93.75), but the whole dataset ranged from 20 to 180 minutes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…In the present study, we concluded that age greater than 30 years, a cyst larger than 7 cm in diameter, the presence of a peritoneal implant, and a history of infertility did not affect operative time. However, Gambadauro et al [19] performed a study with 148 patients and reported that a cyst larger than 5 cm in size was significantly correlated with longer operative time (p=0.015). The authors concluded that factors other than size did not affect operative time.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we concluded that age greater than 30 years, a cyst larger than 7 cm in diameter, the presence of a peritoneal implant, and a history of infertility did not affect operative time. However, Gambadauro et al [19] performed a study with 148 patients and reported that a cyst larger than 5 cm in size was significantly correlated with longer operative time (p=0.015). The authors concluded that factors other than size did not affect operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Otörler bu bulgu dışında diğer faktörlerin operasyon süresini etkilemediği sonucunu bildirmişlerdir. [19] Çalışmanın birçok değer azaltıcı yönü bulunmaktadır. Çalışmanın retrospektif olması, hasta sayısının kısıtlılığı ayrıca hasta takip süresinin kısıtlı olup infertil hastalarda daha sonraki dönemde fertilite yönünden takiplerinin olmaması çalışmanın değer kısıtlayıcı yönleri olarak sayılabilir.…”
Section: Discussionunclassified